2015
DOI: 10.1111/pedi.12276
|View full text |Cite
|
Sign up to set email alerts
|

Leptin but not adiponectin is related to type 2 diabetes mellitus in obese adolescents

Abstract: Because adiponectin levels did not differ between obese adolescents with and without T2DM, hypoadiponectinemia as observed in obesity seems not to be involved in the genesis of T2DM. The relative hypoleptinemia in obese adolescents with T2DM as compared with obese adolescents without T2DM may contribute to the development of T2DM. Future longitudinal studies in humans are necessary to prove this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 53 publications
1
18
0
1
Order By: Relevance
“…Adolescents with T2DM were recruited from the DPV dataset (for details of this cohort see (2,25)). Briefly, T2DM was diagnosed based on the criteria of the American Diabetes Association identical to German guidelines (26).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents with T2DM were recruited from the DPV dataset (for details of this cohort see (2,25)). Briefly, T2DM was diagnosed based on the criteria of the American Diabetes Association identical to German guidelines (26).…”
Section: Subjectsmentioning
confidence: 99%
“…Numerous adipose tissue-derived hormones have been shown to predict T2DM and to be involved in the pathogenesis of T2DM. For example, we have recently reported that leptin levels but not adiponectin levels differ between obese adolescents with and without T2DM (2). Moreover, recent data revealed increasing evidence that also liver-derived hormones might affect glucose metabolism.…”
mentioning
confidence: 98%
“…However, this would be rather an indirect/downstream effect on serum leptin levels than an effect of polymorphisms directly acting on LEP gene transcription and protein expression, and the hypothesis is not yet proven. In contrast, in a recent but small study, leptin levels were shown to be significantly lower in an adolescent group with T2D compared to a BMI-, age-, and gender-matched control group without T2D (74 in each group), with equal adiponectin levels in both groups [62].…”
Section: Leptin (Lep)mentioning
confidence: 61%
“…leptin levels were shown to be significantly lower in an adolescent group with T2D compared to a BMI-, age-, and gender-matched control group without T2D (74 in each group), with equal adiponectin levels in both groups [62].…”
Section: Leptin (Lep)mentioning
confidence: 84%